Effect of combined contraceptive pill on immune cell of ovarian endometriotic tissue - Wanwisa Waiyaput; Keerati Wattanakamolchai; Yada Tingthanatikul; Srithean Lertvikool; Siriluk Tantanavipas; Kanthanadon Dittharot; Morakot Sroyraya; Areepan Sophonsritsuk (BMC, 2021)
Abstract Background Dysregulation of immune response is associated with development of endometriosis. The study aim was to evaluate effect of combined oral contraceptive pills (COCs) consisting of ethinyl estradiol (EE) and desogestrel on the expression of macrophage, natural killer cells, and regulatory T cells of ovarian endometriotic cysts. Methods Endometriotic cyst wall tissues were collected from women with endometriosis who were treated (n = 22) with COCs (one table per day of EE 0.03 mg and desogestrel 0.15 mg administered for 28 to 35 days before surgery) or untreated (n = 22). The tissues were collected from endometriotic cyst wall during laparoscopic or laparotomy ovarian cystectomy. Immunohistochemistry for anti-CD68, anti-CD56, and anti-forkhead-winged helix transcription factor (FoxP3), a marker for macrophages, natural killer cells, and regulatory T cells, respectively, were investigated. Results The median (interquartile range [IQR]) number of anti-CD68 positive cells in the COC group was significantly lower than in the untreated group (12.7; 4.9-19.3) versus 45.7 (26.0-70.7), p < 0.001). Tissue infiltration of anti-CD56 positive cells in endometriotic cyst was significantly higher after the treatment when compared with tissue from untreated group (42.9, 27.4-68.9 versus 25.3 (14.1-37.3; p = 0.009). The number of regulatory T cells was also significantly increased in the COC group (6.3, 2.8-15.5) versus 0 (0-1.8; p < 0.001). Conclusions The effects of COC, containing EE 0.30 mg with desogestrel 0.15 mg, on the immune system was demonstrated by a significant decrease in the number of macrophages and an increase in natural killer and regulatory T cells.